Pour une « métascience » du paysage - Hervé Brunon; Catherine Chomarat-Ruiz; Pierre Donadieu; André Torre (Projets de Paysage)
This paper presents a research whose aim is to develop a « metascience » of landscape. It recounts the origins of this program, focusing on the issue of landscapes transmission à hybrid legacy between nature and culture. It points out the non-scientific cha¬racter of the criticism in charge of qualifying the value of landscape and the inadequacy of an interdisciplinary approach to support this practice of expertise. This paper proposes to enlighten this ethical issue by a new science able to exceed the dichotomy between nature and culture, on which are based all the sciences of landscape. Developing this new science requires a critical history, or better, what we would call an epistemology of the « protosciences » of landscape (i.e. an analysis of landscape in all its components, human and natural). Lastly, this article considers the new paradigm implied by this metascience for the landscape disciplines as for the others disciplines addressing the nature/culture issue.